Planetary diversity : rocky planet processes and their observational signatures - Tasker, Elizabeth J.; Unterborn, Cayman; Laneuville, Matthieu, 1987-; Fujii, Yuka; Desch, Steven J., 1970-; Hartnett, Hilairy E. (IOP (Series). Release 21., 2020)
The last thirty years have seen an irrevocable change in the field of planetary science with the discovery of the first planets around stars other than our own Sun. While approximately twenty percent of the exoplanets we have discovered are close in size to the Earth, the similarity of their surface environment to our home world remains unknown. This book presents an exploration of the potential diversity of rocky planets through a quantitative study of how planetary processes change as properties deviate from the Earth. Changes in four specific properties are considered: the presence of a magnetic field, the production and loss of internal heat, planetary composition and volatile abundance.